Challenges in Implementing Kurikulum Merdeka for EFL Teachers - Fahrani Reza; Zuliati Rohmah; Nur Nabilah Abdullah (JEELS (Journal of English Education and Linguistics Studies), 2023)
Indonesia's new Kurikulum Merdeka, introduced for post-COVID-19 recovery and educational improvement, presents unique challenges, especially requiring teachers to create teaching materials from scratch. This article explores the challenges the English teachers face in executing Kurikulum Merdeka. This study employed a mixed-method approach to examine the challenges faced by English teachers when implementing Kurikulum Merdeka. Quantitative data were collected through a Google Form questionnaire distributed to 170 English teachers in secondary schools across Indonesia. Qualitative insights were obtained through two separate Focus Group Discussions (FGD) sessions, one involving junior high school (SMP) teachers and another with high school (SMA) teachers, in the cities of Malang and Mataram, Indonesia. The current study unveils a myriad of challenges faced by English teachers in connection with the curriculum. These challenges are ascribed to various factors encompassing insufficient teacher training, limited access to support facilities, reduced self-efficacy levels, inadequate information technology skills, students' diverse backgrounds, financial constraints, limited resources, comprehension and implementation obstacles associated with differentiated learning strategies, and issues related to time allocation and management.